Two cycloartanes-type triterpenoid from Homonoia riparia Lour - Huyen, Le Thi; Son, Nguyen Thi; Kiem, Phan Van (Vietnam Journal of Chemistry, 2017)
Using various chromatography methods, two known cycloartanes, 24-methylenecycloartane-3β,6β,7β,16β-tetraol (1) and riparsaponin (2), together with two known flavonol glycosides, quercetin 3-O-β-D-glucopyranoside (3) and quercetin 3-O-α-L-rhamnopyranosyl (1→6) β-D-glucopyranoside (4) were isolated from the methanol extract of the leaves of Homonoia riparia Lour. Their structures were determined by MS and 1D-, 2D-NMR spectra, as well as by comparison with those reported in the literature. Keywords. Homonoia riparia, cycloartane, flavonol glycoside.